PROJECTION ON FICTIONAL CHARACTERS AS AN EMOTIONAL CATALYST - Rujina, Valeria (E-Journal VFU, 2024)
An analysis using the methodology of critical psychology regarding theemotional connection between people and fictional characters. A deeper look into the ancienttradition of human art and storytelling through the lens of social psychology. Comparison betweenmodern approaches towards creating characters and their perception and the approaches of the past.Analysis of the way stories influence society and the way society influences stories. Personalgrowth via imagination and entertainment
Keywords: media influence; literature; social psychology; emotional attachment; art